2010
DOI: 10.1002/cphc.201000537
|View full text |Cite
|
Sign up to set email alerts
|

A Carbon/Titanium Vanadium Nitride Composite for Lithium Storage

Abstract: In recent years, substantial efforts have been made with regard to the explorations of novel anode materials for lithium batteries with superior recharging-ability and minimal capacity fade. Among a variety of options, carbonaceous materials are promising candidates.[1] Graphite is widely used nowadays as anodes in commercial cells, [2] nevertheless its capacity is restricted to 372 mAh g À1 (maximum stage by forming LiC 6 ).Therefore, extensive research is currently focusing on the electrochemical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…In order to improve the rate capability of NiCo2O4 electrodes, we introduced titanium nitride (TiN) to form NiCo2O4@TiN core-shell nanostructures with NiCo2O4. TiN attracted our attention due to the following reasons: 1) TiN is already commonly used in industry for electronics and wear resistance applications due to its low cost, scalability, and superior corrosion resistance [46,47]; 2) as a metallic material, TiN offers superb electrical conductivity (4000-55500 S cm -1 ) and mechanical stability [48][49][50]; 3) previous reports have demonstrated that transition metal nitrides are capable of delivering high energy and power density as supercapacitor electrodes [51,52]. Meanwhile, by employing atomic layer deposition (ALD), we were able to conformally grow a TiN shell onto complex nanostructures such as the NiCo2O4 nanofiber arrays without altering the desired structural features of the underlying NiCo2O4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the rate capability of NiCo2O4 electrodes, we introduced titanium nitride (TiN) to form NiCo2O4@TiN core-shell nanostructures with NiCo2O4. TiN attracted our attention due to the following reasons: 1) TiN is already commonly used in industry for electronics and wear resistance applications due to its low cost, scalability, and superior corrosion resistance [46,47]; 2) as a metallic material, TiN offers superb electrical conductivity (4000-55500 S cm -1 ) and mechanical stability [48][49][50]; 3) previous reports have demonstrated that transition metal nitrides are capable of delivering high energy and power density as supercapacitor electrodes [51,52]. Meanwhile, by employing atomic layer deposition (ALD), we were able to conformally grow a TiN shell onto complex nanostructures such as the NiCo2O4 nanofiber arrays without altering the desired structural features of the underlying NiCo2O4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[6a] Moreover, it is confirmed that VN delivers a large reversible capacity of approximate 1200 mAh g −1 , much higher than abundant of various metal nitrides previously reported because of the high valence (+3) of V in VN. Thus, VN nanoparticles, porous VN, and VN‐based composites have been widely synthesized for lithium storage by magnetron sputtering,[6a] template‐assistant, and chemical vapor deposition methods . Unfortunately, VN materials commonly accompany large volume change (≈240%, calculated based on the density of VN, Li 3 N, and V) during cycle processes, leading to severe particle–particle electronic contact loss and poor cycle performances for lithium storage.…”
mentioning
confidence: 99%
“…Obviously, such high‐rate performances of G‐VNQD‐500 are superior to those reported for the most previously VN‐based materials including VN films, porous VN, Ti–VN and VN–carbon composites. [6b,c],[9a] To explore the reason of the excellent electrochemical behaviors of G‐VNQD‐500, electrochemical impedance spectroscopy (EIS) measurements were carried out after rate cycles (Figure f, Figure S6 and Table S2, Supporting Information). Interestingly, the solid electrolyte interface (SEI) and charge transfer resistances of G‐VNQD‐500 electrode are only 23.9 and 60.8 Ω, which is much lower than those of pure VN electrode (30.9 and 135.3 Ω).…”
mentioning
confidence: 99%
“…(TiN)具有良好的导电性和高温化学稳定性 [23] , 而文 献报道的氮化钒(VN)显示出巨大的储锂容量. 基于 [24] (如图 3 所示), 将两种氮化物的优势协同 [25] . 我们课题组在氮掺杂对石墨烯结构与储锂物…”
Section: 了一系列纳米结构混合传输(电子和离子)电极材料unclassified